Evaluation of In-vitro free Radical Scavenging Potential of Whole Plant of Pupalia Lappacea Juss (L) - P. Veeramani (Journal of Global Pharma Technology, 2018)
The study was designed to examine the in vitro antioxidant activities of ethanolic extract of whole plant of Pupalia lappacea. The antioxidant activity was evaluated by DPPH radical scavenging, Nitric Oxide Scavenging and Iron chelating activity with reference standard Rutin, Ascorbic acid and EDTA respectively content was estimated. Our results indicate that ethanolic extract of Pupalia lappacea has IC50 value of 510 μg/ml, 410 μg/ml, 310 μg/ml of DPPH, nitric oxide, and iron chelating activity respectively. So, the in-vitro studies clearly showed that the ethanolic extract of Pupalia lappacea has a significant antioxidant activity. These in-vitro assays wise that this plant extract is the best root of natural antioxidant; these are very supportive in the progress of preventing different types of oxidative stresses.Keywords: Pupalia lappacea, DPPH assay, Nitric oxide radical scavenging, Iron chelating activity.